Effect of Anterior Chamber Instability during Phacoemulsification Combined with Intraocular Lens Implantation. (23rd February 2022) - Geng, Wenjing; Lin, Wenli; Song, Pei; Zhang, Min; Wu, Jian; Su, Shu; Yuan, Yurong; Ji, Min; Guan, Huaijin
Abstract : Purpose . To determine the incidence of anterior chamber (AC) instability during phacoemulsification (phaco) combined with intraocular lens implantation and investigate its effect on intraocular tissues. Methods . Among the 248 enrolled eyes, 121 and 127 eyes were categorized into the irrigation and nonirrigation groups, respectively, depending on the use of a self-made anterior chamber maintainer (ACM) during phaco. AC stability was evaluated using operating microscopy and intraoperative optical coherence tomography (iOCT). Slit-lamp examination of AC flare and cells was performed 1 day postoperatively. Corrected distance visual acuity (CDVA), intraocular pressure (IOP), endothelial cell density (ECD), central corneal thickness (CCT), posterior vitreous detachment (PVD), and central foveal thickness (CFT) were evaluated preoperatively and at 1 week, 1 month, and 3 months postoperatively. Results . There was good consistency in AC stability evaluation between operating microscopy and iOCT. The incidence of AC instability was significantly different between groups after the phaco and irrigation/aspiration tips were withdrawn from the AC P < 0.001 . At 1 day postoperatively, after excluding eyes in which the AC could not be visualized, AC cell grades were significantly lower in the irrigation group ( P = 0.014). There was no significant difference in CDVA, IOP, ECD, and CCT between groups during the 3-month follow-up P > 0.05 . At 1 month and 3 months postoperatively, PVD occurred in 8 (16.3%) and 14 (28.6%) eyes and in 22 (40.7%) and 37 (68.5%) eyes in the irrigation and nonirrigation groups, respectively ( P = 0.006 and P < 0.001 ). CFT was significantly higher in the nonirrigation group at 1 and 3 months postoperatively ( P = 0.018 and P = 0.010). Conclusions . Both operating microscopy and iOCT are efficient for AC stability evaluation. When the phaco and I/A tips were withdrawn from the AC, there was frequent instability. Intraoperative AC instability can increase surgery-induced inflammation and lead to postoperative complications such as PVD, retinal detachment, and macular edema. The self-made ACM can effectively reduce the incidence of intraoperative AC instability and these complications.